1997
DOI: 10.1007/bf02463286
|View full text |Cite
|
Sign up to set email alerts
|

Corticofugal influences on the neurons of different regions of the hypothalamus

Abstract: Responses of the neurons of the lateral and ventromedial hypothalamic regions (HL and Hvrn, respectively), as well as of the area of the dorsal hypothalamus (arid) and the projection region of the medial forelimb bundle (MFB), evoked by stimulation of the proreal cortex (field 8), cingular cortex (field 24), pyriform Iobula (periamigdalar cortex), and hippocampus (CA3) were studied in acute experiments on cats under ketamine anesthesia. Distributions of the latent periods of the responses recorded from hypotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…We found that these are the hypothalamic regions with the maximum number of the neurons responding to stimulation of the neoarchipaleocortex. There are two main loci of convergence of the influences arriving at hypothalamic neurons [6,7 ]; one such focus is localized …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that these are the hypothalamic regions with the maximum number of the neurons responding to stimulation of the neoarchipaleocortex. There are two main loci of convergence of the influences arriving at hypothalamic neurons [6,7 ]; one such focus is localized …”
Section: Resultsmentioning
confidence: 99%
“…The responses were evoked by single and repeated (serial, 6 to 300 sec 1) stimulations of the proreal (field 8) and cingular (field 24) cortices, pyriform lobe (periamygdalar cortex), and hippocampus (CA3). Surgical procedures and the course of experiment were described earlier [7] in more detail.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations